Інформаціоналізм: метаморфози суспільства і політики - Городецький, О.О. (Збірник наукових праць "Політологічні студії", 2011)
У статті автор, поєднуючи дескриптивний та аналітичний методи, намагається ідентифікувати типологічні ознаки інформаціонального суспільства, що інтегративно виявляють себе у глобальному та локальному (регіональному) функціонуванні економіки, соціальних мереж, політики, культури та науки. Стверджується, що хронологічні параметри ідентифікації різних етапів еволюції суспільства є другорядними, несуттєвими у межах політичної науки; на то місце пропонується матриця сутнісних логічних ознак, яка побудована на взаємодії позаекономічних, власне економічних (інструментальних) та надекономічних (символічних) аргументів суспільної архітектури, що дає можливість адекватно описати траєкторії політики та влади в сучасному глобальному світі. For the last 40 years the research on politics and power within a post-industrial system has remained a strong scientific tradition in the Western schools of sociology and political science. By applying descriptive and analytical methods, the author endeavors to identify typological characteristics of informational society which in an integrated way emerge in the global and local (regional) functioning of economy, social networks, politics, culture and science. It is maintained that in political science the chronological parameters of identification of various stages of society evolution are of secondary, insignificant importance. Instead it is proposed that its place should be taken by the matrix of substantial logical characteristics built on the interplay of extra-economic, economic and super-economic (symbolic) arguments of social architecture, which offers a possibility to appropriately describe the trajectories of politics and power in the modern global world.